EXPLORING TEACHER'S IMPLEMENTATION OF AUDIO LINGUAL METHOD, CHALLENGES, AND TECHNIQUES FOR IMPROVING STUDENT'S VOCABULARY MASTERY - Suwarno, Tono Suwarno; Retnowati, Nanik; Sundari, Hanna (ENGLISH JOURNAL, 2023)
This study aimed to explore the EFL teacher's implementation of the Audio-lingual Method, investigate his challenges and explain his technique to improve students' vocabulary mastery. The case study was carried out in SMA Pasundan Cikalongkulon Cianjur. The respondents were 32 students and an English teacher chosen purposively to be involved in this study. The instruments of data collection were observation and interview. The result showed that the EFL teacher implemented Audio-lingual Method well. It was proved that he applied its principles namely imitation, using the target language communicatively, separating the native and the target language linguistic system, modeling, repetition, reinforcement, verbal and nonverbal stimuli, and English culture. Moreover, the student's average score improved, There were some challenges namely limited time, student motivation, different capabilities, and the classroom condition. Moreover, there were some techniques such as dialog memorization, repetition drill, transformation drill, and question and answer drill, and the most applied techniques were repetition drill, transformation drill, and question and answer drill. It is recommended that English teachers implement Audio-lingual Method for teaching vocabulary. Further study could be conducted to investigate how the students feel when learning vocabulary using the Audio-lingual Method.